Managing patient emotions as skilled work and being 'one of us'. (October 2015) - Kessler, Ian; Heron, Paul; Dopson, Sue
While the literature on emotional labour has concentrated on worker feelings, this article assesses the capacity of an occupational role to deal with the feelings of the service user and, in particular, whether this capacity constitutes a skill. It focuses on the healthcare assistant, an unregulated role increasingly important in the delivery of hospital care. The capacity of this role to manage the emotions of patients has been questioned. However, drawing upon case study data, the role is presented as an effective manager of patient emotions, an outcome partly related to the HCAs' abilities, but more closely to the patients viewing HCAs as 'one of us'.